Concept Paper on the Recommendations for the Improvement of the Operating Guidelines for the Integration Special Education Program in Malaysia - Zulkifli, Zulhafizsyam Bin; Anal, Ardzulyna Binti (Angstrom Centre of Education, 2023)
This study aims to improve the operating guidelines of the Special Integration Education Program (PPKI) in Malaysia through qualitative methodology. The problem statement for this study is the insufficient operational guidelines for the Integrated Special Education Program, leading to sub-optimal results for students with special educational needs. Research objectives include identifying key challenges in the implementation of Special Integration Education Program operating guidelines, exploring stakeholders' perspectives on the current system, and developing recommendations to improve Special Integration Education Program operating guidelines. The literature review highlighted previous studies on the subject, emphasizing the need for a more comprehensive approach to the operationalization of Integrated Special Education Programs. The conceptual framework shows how the research will be conducted, using qualitative methods such as semi-structured interviews and focus group discussions. The findings are expected to contribute to the improvement of the implementation of the guidelines for the operation of the Integration Special Education Program in Malaysia, which will ultimately benefit students with special education needs.